الحياة العلمية في قلعة بني حماد(398-547هـ /1007-1152م) - يحي سمية; معامير عائشة (جامعة الوادي - University of Eloued, 2025)
كانت قلعة نني حماد الواقعة في شمال شرف -الجزائر واحدة من أبرز مراكز العلم والثقافة في المغرب الأوسط خلال ‏القرن 11 الميلادي، ولقد ازدهرت الحياة العلمية بعاصمة الحمايتين بفضل رعاية الأمراء الحماديين للعلماء ‏وتشجيعهم على البحث والتعليم، وقد عرفت القلعة باحتضارها. لعدد كبير من العلماء والفقهاء خاصة في مجال ‏الفقه الاسلامي: الحديث التفسير اللغة العربية، حيث كان المذهب المالكي سائداً، كما شهدت الحياة الأدبية ‏بالقلعة نشاطا ملحوظا من خلال الشعر والمناظرات التي كانت تقام في بلاط الحكام مما ساهم في تطوير اللغة ‏والأدب العربي من خلال ولم تكن العلوم الدينية وحدها مزدهرة، بل كان هناك اهتمام ايضا بالعلوم التطبيقية. ‏كالرياضيات والهندسة، ويتجلى ذلك في الطراز المعماري المتقدم للقلعة الذي قلعة يعكس براعة علمية وفنية كما ‏كانت القلعة مركزا للتبادل الثقافي والفكري، حيث استقطبت العلماء من مختلف انحاء المغرب الإسلامي مما جعلها ‏نقطة إشعاع علمي في العصر الوسيط.‏ The castle of Bani Hammad, located in northeastern Algeria, was one of the most prominent centers of science and culture in central Magreb during the 11th century AD and scientific life flourished in the capital of the Hammadis thanks to the care of the Hammadi princes of scientists and encourage them to research and education , and the castle was known to embrace a large number of scientists and jurists, especially in the field of Islamic jurisprudence, hadith, interpretation, Arabic language. The literary life of the castle also witnessed remarkable activity through poetry. And the debates that were held at the court of the rulers. Which contributed to the development of language and literature, and religious sciences were not only prosperous, but there was also interest in applied sciences such as mathematics and engineering, and this is reflected in the advanced urban style of the castle, which reflects scientific and artistic prowess, as it was the center of cultural and intellectual exchange, as it attracted scientists from different parts of the Islamic Maghreb, making it a point of scientific radiation in the Middle Ages.
مذكرة ماستر قسم علوم انسانية تخصص تاريخ الغرب الباسلامي في العصر الوسيط
Keywords: خمس عبارات درنا; العلوم العقلية; العلوم النقلية; Sciences transmises; Sciences rationnelles; Cinq phrases Darna